Behaviors at a high ambient temperature of binary mixture single droplets containing pentadecane and dodecane at various volume ratios - W. Manosroi (2018)
© 2017 IEEE. This study has aimed to investigate the behaviors including evaporation rates, refractive index, volume fractions and mixing characteristics of the binary mixture single droplets containing pentadecane (C-15) and dodecane (C-12) in a heated chamber at a high ambient temperature of 98°C. The volume ratios of pentadecane to dodecane were 3:1, 1:1 and 1:3. The droplet diameter was measured at the forward scattering region while the droplet refractive index was measured at the backward scattering region, and the volume fractions of the binary mixtures were determined from the refractive index. The time dependent changes of the droplet diameters were calculated from the Morphology Dependent Resonances (MDRs) from the refractive index. The evaporation rate of the binary mixture droplets were between the evaporation rate of pentadecane and dodecane single component droplet as well as the refractive index. The pentadecane volume fractions in the mixture were increased. The results from this study can be applied for a better understanding of fuel droplet evaporation in a combustion chamber.